Body Practice Management: from Tradition to Modern (on the Example of Yoga Practices) (Laisvalaikio tyrimai, 2021)
Research object. The modern culture of the West was formed under the pressure of metaphysical discourse with its ontological and epistemological tensions, relying on a rigidly acting subject of a constitutional nature with its characteristic opposition - “spiritual-bodily”. The author tries, through a thorough study of the structure of the body, its functional significance, to show the ability to control it and even design it. Yoga practices allow you to look at the human body in a new way. They also contribute to the creation of a special cognitive situation around the topic of body and bodily control. This opens up completely new horizons of life for a certain part of the population and the opportunity to invest knowledge in the process of constructing the corporeal. The formula "Do yourself by yourself" activates the desire to create personal reality and adjusts to certain management practices - anthropotechnics. The article confirms the idea of ​​the integrity of the spiritual and bodily, which Yoga has never lost.The problem is the study is what knowledge about the body underlines the special mission of Yoga to help maintain a special understanding of bodily control, in particular, as a stepping stone to spiritual growth and how it changes in the context of tradition and modernity.Purpose of the study: on the basis of the analysis of the bodily practices of Yoga, presented in the ancient texts of Yoga, to come to an understanding of the body as a constructivist practice, and to regard its management as a step towards the spiritual growth of a person.Research methods. Scientific literature analysis, synthesis, generalization. Scientific literature and theoretical interpretation in order to summarize the research carried out on this topic. The analysis of the control of the body and bodily practices was carried out. Its ontological and anthropological dimensions will contribute to the understanding that the body can be an instrument of a person-yoga on the path of ascent to the spiritual, and the phenomenological and epistemological dimensions will emphasize the constructivist nature of the action with it.Outcomes and conclusions. According to ancient texts, a person's thoughts were based on the starting point - the human individual, from his psychosomatic system. The practice of Yoga introduced the element of bodily control into the culture of the West as a component of spiritual, social and physical life; it became one of the many responses to the challenges of the crisis of the culture of the West. Awareness of such dimensions of the body as sotereological, ontological, epistemological and phenomenological contribute to the creation of a special cognitive situation around the topic of body and bodily control. This opens up completely new horizons of life for a certain part of the population and the opportunity to invest knowledge in the process of constructing the corporeal. The “Do It Yourself” formula activates the desire to create personal reality and tune in to certain practices. The knowledge of the body, which we find in ancient texts and on which Yoga is based, once again emphasize the special mission of Yoga. It encourages us to study our basic outlook on life, to find out which of them are non-functional in a given time, aims us at replacing them and at finding the most suitable ones for our time.Key words: Yoga, bodily practices, construction of the bodily, the body as a construct.